Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics: System Demonstrati 2021
DOI: 10.18653/v1/2021.eacl-demos.20
|View full text |Cite
|
Sign up to set email alerts
|

MadDog: A Web-based System for Acronym Identification and Disambiguation

Abstract: Acronyms and abbreviations are the shortform of longer phrases and they are ubiquitously employed in various types of writing. Despite their usefulness to save space in writing and time in reading, they also provide challenges for understanding the text especially if the acronym is not defined in the text or if it is used far from its definition in long texts. To alleviate this issue, there are considerable efforts both from the research community and software developers to build systems for identifying acrony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Early work observed that acronyms and their long forms appear frequently together in a document, as in "Artificial Intelligence (AI)". Based on this pattern, many approaches identify and extract acronyms by using rules (Yeates et al, 2000;Larkey et al, 2000;Pustejovsky et al, 2001;Park and Byrd, 2001;Yu et al, 2002;Schwartz and Hearst, 2002;Adar, 2004;Ao and Takagi, 2005;Okazaki and Ananiadou, 2006;Sohn et al, 2008;Veyseh et al, 2021) or supervised methods (Chang et al, 2002;Nadeau and Turney, 2005;Kuo et al, 2009;Movshovitz-Attias and Cohen, 2012;Liu et al, 2017;Wu et al, 2017;. In our work, we build on previous work (Schwartz and Hearst, 2002) for Acronym Identification, and focus mainly on disambiguation.…”
Section: Acronym Identification and Disambiguationmentioning
confidence: 99%
See 2 more Smart Citations
“…Early work observed that acronyms and their long forms appear frequently together in a document, as in "Artificial Intelligence (AI)". Based on this pattern, many approaches identify and extract acronyms by using rules (Yeates et al, 2000;Larkey et al, 2000;Pustejovsky et al, 2001;Park and Byrd, 2001;Yu et al, 2002;Schwartz and Hearst, 2002;Adar, 2004;Ao and Takagi, 2005;Okazaki and Ananiadou, 2006;Sohn et al, 2008;Veyseh et al, 2021) or supervised methods (Chang et al, 2002;Nadeau and Turney, 2005;Kuo et al, 2009;Movshovitz-Attias and Cohen, 2012;Liu et al, 2017;Wu et al, 2017;. In our work, we build on previous work (Schwartz and Hearst, 2002) for Acronym Identification, and focus mainly on disambiguation.…”
Section: Acronym Identification and Disambiguationmentioning
confidence: 99%
“…• MadDog (Veyseh et al, 2021) is a web-based acronym disambiguation system for multiple domains. It first creates chunks in which all samples with the same acronyms are assigned to the same chunks.…”
Section: A3 Competitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although aimed for text-dense documents, the acronym disambiguation approach proposed by [36] has potential. A dictionary is created by scraping multiple websites which are dense in acronyms and their corresponding long forms (e.g.…”
Section: ) Abbreviation Disambiguation (Ad)mentioning
confidence: 99%
“…Because AD is context-dependent, there is no definitive solution proposed that can be directly implemented into this application. Despite that, the web-scraping approach by [36] is modified to be specialized for receipt item names. Since AD in receipts is only used in the search function, the disambiguated words are not visible or displayed to the user.…”
Section: Decision Of Algorithmmentioning
confidence: 99%